Tailoring Cellular Uptake of Gold Nanoparticles Via the Hydrophilic‐to‐Hydrophobic Ratio of their (Co)polymer Coating. (13th May 2015) - Zhang, Zhiyue; Van Steendam, Katleen; Maji, Samarendra; Balcaen, Lieve; Anoshkina, Yulia; Zhang, Qilu; Vanluchene, Glenn; De Rycke, Riet; Van Haecke, Frank; Deforce, Dieter; Hoogenboom, Richard; De Geest, Bruno G.
Abstract : It is demonstrated how cellular uptake and protein corona of (co)polymer‐coated gold nanoparticles can be altered by the hydrophilic‐to‐hydrophobic comonomer ratio. A novel, label‐free flow cytometry strategy is developed to investigate particle uptake. These findings offer insight in the design and analysis of hybrid nanomaterials for interfacing with biological systems. Abstract : Cellular uptake of gold nanoparticles depends on the hydrophilic‐to‐hydrophobic balance of the (co)polymer coating as shown by a novel flow cytometry strategy.